Review: Technology, Chemistry and Microbiology of Whey Cheeses - Pintado, M. E. (2011)
In whey cheese manufacture, whey, plain or added with milk, is heated by direct fire, bubbling steam or alternatively in jacketed vats. In some cases, salt s or organic acids are previously added. At 80-85 OC, the first particles of curd form; at 85-95 'C, the curd may be cooked for a few minutes to reduce moisture content and/or to obtain the desirable level of browning. After drainage at room temperature during molding for ca. 4 h, whey cheese is stored at ca. 4 'C. The typical mass yield is 6%, but addition of milk, calcium salts and preliminary concentration of protein (by condensation or ultrafiltration techniques) may increase yield considerably. Some types of whey cheeses are supposed to be consumed within a short time upon manufacture (e.g., Ricotta, Requeijdo and Manouri), whereas others bear a longer shelf life (e.g., Gjetost, Mysost and Myzithra). Whey cheeses are significantly different from one another in terms of chemical composition, which is mainly due to variations in the source and type of whey, as well as to the processing practices followed. Moisture content and pH of whey cheeses are usually high and favor microorganism growth (molds, yeasts, lactic acid bacteria and Enterobacteriaceae account for the dominant microflora in these cheeses). Adequate packaging of whey cheeses should be provided, and legislation should be prepared to fix standard characteristics of each type of whey cheese, and hence protect typical products from adulteration and fakes. Marketing efforts should also be aimed at increasing whey cheese consumption, either directly or incorporated in desserts, snack dips and pasta-type dishes.